Social sustainability of neighborhood parks in India: A systematic review of gaps and directions for further investigation. - Haskaran, Rekha Hajela, Amit and Dewan, Anil (Nagarlok: Quarterly Journal of Urban Affairs)
Social sustainability is a key goal to be achieved in the built environment of cities. There is a need to operationalise the concept at the neighbourhood scale. This can be done by formulating context-specific objectives for planning and designing public spaces in the neighbourhood that are conducive to promoting social sustainability. Neighbourhood parks as public spaces at this scale can effectively create socially sustainable neighbourhoods in global south cities. Despite extensive theoretical literature on social sustainability, there is a lack of evidence-based empirical research on its relation to neighbourhood parks, especially in the urban Indian context. Therefore, this study aims to understand the gaps in the operationalisation of the concept and uncover areas for further examination for future research through a systematic literature review. The results indicate a western predominance with fewer studies in the Indian cities on social sustainability at the neighbourhood park scale. The study recommends future empirical research to investigate key components of social sustainability such as social interaction, social cohesion, participation, community building, place attachment, safety, and equity in relation to park quality, usage and participative management, etc. to formulate an evidence-based systematic assessment framework and methodology for neighbourhood parks.- Reproduced
Keywords: Sustainability, Neighborhood parks, Systematic review